Студенттерде кәсіби құзыреттілікті дамыту мәселесі - Кабдуалиева, Э.Ж. (My University, 2013)
he paper examines the main characteristics of the formation of professional competence of students. The analysis of pedagogical approaches informing a professional relationship with competence and personal development of youngpeople.